Dynamic deformation–dependent magnetic field–induced force transmissibility characteristics of magnetorheological elastomer. (July 2017) - Poojary, Umanath R; Hegde, Sriharsha; Gangadharan, KV
The need for broad-band vibration isolation performance of the structures is fulfilled by magnetorheological elastomer–based smart vibration isolation system. The smart isolation capabilities of magnetorheological elastomer isolator vary with the input dynamic deformation levels. In this study, force transmissibility measurement approach is adapted to evaluate the influence of dynamic deformation on the field-induced isolation capabilities of magnetorheological elastomer. The variation in isolation capabilities of magnetorheological elastomer is assessed in terms of isolation effect. Isolation performance of magnetorheological elastomer is enhanced with the increase in the magnetic field. Under increased dynamic deformation levels, the isolation characteristics of magnetorheological elastomer are influenced by the Payne effect. Dominance of the Payne effect under non-magnetized state of magnetorheological elastomer has enhanced the isolation effect at larger strain levels. The influence of strain on isolation characteristics of magnetorheological elastomer is verified from the magnetic force simulation between a pair of dipoles performed in ANSYS (version 14).